Annual Plan 1997-98 Volume-I Planning Institutional Finance and Statistics and Science and Technology Department - Planning Commission (Planning Commission, 1997)
The approved outlay for the Eighth Five Year Plan at Rs.12300 crores at 1991-92 prices was more than double the Seventh Plan level of Rs.3500 crores. Against annual approved outlays of Rs.16150 crores, expenditure has fallen short by 8.0 per cent at Rs.14894 crores. In real terms this is 8.3 per cent less (Rs.11272 crores) than the Eighth Plan approved outlay of Rs.12300 crores, although still almost double that during the Seventh Plan.
Planning Institutional Finance and Statistics and Science and Technology Department
Planning, Institutional Finance and Statistics and Science and Technology Department